Kualiti perkhidmatan awam menurut perspektif Islam - Ilhaamie Abdul Ghani Azmi; Sharifah Hayaati Syed Ismail al-Qudsy; Siti Arni Basir (Penerbit Universiti Malaya, 2013)
Quality services in public sector management in Malaysia according to Islamic perspectives